Purificación y caracterización parcial de una toxina (Hm3) del veneno de Hadruroides mauryi (Francke y Soleglad, 1980) (Scorpiones, Iuridae) - Velásquez, Luz (2004)
A toxin (Hm3) was purified from the scorpion venom Hadruroides mauryi, by ion-exchange chromatography on CM-Sephadex C-25 with 0,05M ammonium acetate buffer pH 7. The toxin produce contraction and immobilize the inoculated limb of white mice, and is a basic protein with a molecular weight of 4,5 kDa. After of 45 minutes inoculated in gastrocnemius muscle of white mice, Hm3 (30,4 µg) increases the plasmatic level of creatine kinase from 252,6 UI/L to 3779,3 UI/L and lactate deshidrogenase from 142,7 UI/L to 248,2 UI/L; likewise increases the level of intramuscular calcium from 34,1 nmoles to 69,3 nmoles. This toxin have not proteolitic or phospholipase activity.